Beyond Expertise: Teacher’s Strategies, Student Engagement, and Academic Performance - Vesagas, Honey Vie H.; Lantaka, Ivy A. (International Journal of Research in Interdisciplinary Studies, 2025)
This study aimed to examine the strategies employed by teachers in teaching subjects beyond their field of specialization and how these strategies affect student engagement and academic performance. Conducted at Labuan Central School in Zamboanga City during the school year 2024–2025, the study involved intermediate-grade teachers and students selected through random sampling. Using a descriptive-correlational design, the research explored three key areas of teacher strategies: lesson planning, classroom instruction, and classroom assessment. Findings revealed that teachers often utilized content-based strategies such as researching topics and using teaching guides and rubrics. However, strategies related to fostering critical thinking, diverse instructional methods, and individualized support were only occasionally applied. Students reported a high level of engagement, particularly in classroom participation and assessment, indicating that they were frequently active and responsive. Their academic performance was categorized as satisfactory, reflecting that they are meeting learning standards but have room for improvement. Correlation analysis showed no statistically significant relationship between teacher strategies and student engagement or academic performance. These results suggest that while teacher strategies are implemented with good intent, other factors may more strongly influence student outcomes. The study concludes that targeted professional development is necessary to equip teachers with more effective pedagogical tools when handling subjects beyond their expertise.